Assessing maximum oxygen uptake through a motor-cognitive reactive agility test in team ball sports athletes - Hülsdünker, T.; Bahdur, K.; Flammang, L.; Naclerio, F.; Sondermann, Y.; Mierau, A.; Karsten, B. (Frontiers in Sports and Active Living, 2026)
Background: Conventional laboratory and field tests often underestimate VO2max and fail to reflect the reactive agility, multidirectional demands of team ball sports. This study examined whether a motor-cognitive Reactive Agility (RA) Test can elicit a true VO2max response and serve as a sport-specific alternative for assessing VO2max in team sport athletes.